Comparing the effectiveness of narrative therapy and EMDR-GTEP protocols in the treatment of post-traumatic stress in children exposed to humanitarian crises - Dozio, Elisabetta; Bizouerne, Cécile; Wamba, Valdes; Atienza, Ninon (Frontiers in Child and Adolescent Psychiatry, 2024)
Background The mental health of children living in humanitarian crisis situations is a major issue. Post-traumatic stress disorder (PTSD) causes great psychological suffering and has negative consequences on children's development. The aim of the study was to analyze retrospective data collected in a mental health and psychosocial support program for children in the Central African Republic, and to compare results of two trauma-focused treatment interventions: the narrative protocol Action contre la Faim (ACF)/KONO; and the EMDR-based Group Trauma Episode Protocol (G-TEP). Both protocols are proposed in a group setting and led by paraprofessionals. Methods In the program, 884 children attended a psychoeducation session and after that, 661 children (290 for ACF/KONO and 371 for G-TEP) benefited from all treatment sessions. PTSD was measured by the Children's Revised Impact of Event Scale (CRIES-8). General distress was measured by the Child Psychosocial Distress Screener (CPDS). Data were collected before and after treatment, and measured 5 months after the end of treatment for 185 children. Results Participants in the ACF/KONO group show a significant reduction on CRIES-8 (t = 44.8; p < 0.001, effect size = 2.63) and CPDS (t = 38.2; p < 0.001, effect size = 2.24). Participants to the G-TEP protocol show a significant effect with reduced scores on the CRIES-8 (t = 49.2; p < 0.001, effect size = 2.55) and CPDS (t = 57.2; p < 0.001, effect size = 2.97). A Student's t-test comparing the ACF/KONO and G-TEP groups shows no significant difference between the two types of treatment between pre- and post-treatment CRIES-8 scores (t = 1.744; p = 0.514, effect size = 0.040) and CPDS scores (t = 1.688; p = 0.092, effect size = 0.323). An analysis of the follow-up data for the 185 children shows that the effects of both protocols are maintained over time with mean scores after treatment and follow-up below the clinical cut-off for both CPDS (<8) and CRIES-8 (<17). Conclusions Both protocols have been shown to be effective in reducing traumatic symptoms in children exposed to conflict; they can be conducted by paraprofessionals and used in humanitarian crisis situations.